Painters participation in the process of Latvia State - formation within the field of art - Grūbe, Signe; Celmiņa-Ķeirāne, Austra (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
Analysis made on contribution of Latvian artists participating in creation of national art during the periods of formation of Latvian nation lets draw a conclusion that Latvian art and its creators – painters have facilitated awareness, formation and content interpretation of nation in Latvia. The signification of visual art is constitutive in a period of formation of a nation, because it gives not only an artist’s interpretation of a situation, but is also available for countless spectators’ interpretations. Artwork makes the idea of nation visible for society. This objective for artwork remains unchangeable further more. Visual image plays significant role in forming collective memory of specific events, memorizing artists’ works as values of national art. The author of the artwork is artist. Artist is a significant participant in nation formation processes, who can help society to identify with nation. This research is made to provide a contribution to understanding of nation concept, drawing attention to the contribution to awareness, consolidation and interpretation of content of nation made by artists as creators of national art. Artists, as it shows the history of art, can set the basic directions of national art by accumulating symbolic capital. They are particular individuals who are able to affect the development progress of national art, as well as historical events. In paper is achieved confirmation of the fact that artists’ strong habitus determine the form and content of national art (J. Grosvalds and V. Purvitis). Latvian painter Romans Suta wrote, “Art is what broadens our conscience, sticks to and delivers something new to the already sensed and understood values. Therefore it is obvious that no society, no nation should not stall in lethargic humbleness, but it must request from its creators – the artists – to deliver continuous movement”. The roots of Latvian art are to be searched in the 2nd part of the 19th century. Boundaries of formation of Latvian national art, like the boundaries of periods of Latvian nation formation and consolidation of the State idea, are up to a point, nonetheless they are tightly interconnected. During the period of national consolidation, analyzed in the work, artists actively participated in social and political processes and depicted them in their works. In this time period there were established that artists were focused not only on the history of Latvian nation, but they were open to new impressions and interested in processes in the field of art of the world. Thereby conclusion can be drew that to be Latvian didn’t mean to be separated from the rest of the world, but vice versa – Latvian can be found only by means of the different. National art was formed not only by selecting and depicting historical ethnic traditions and symbols, but being directly affected by topical events of that moment in Latvia and trends in world’s art and reflecting them in their own expression manner.